Tinjauan Yuridis terhadap Penyelesaian Wanprestasi Perjanjian Asuransi dalam Putusan No. 537/Pdt.g/2013/PN.MDN - Siallagan, Arnol Faisal; Siregar, Taufik (Jurnal Ilmiah Penegakan Hukum, 2017)
Juridical Review Of Completion Of Insurance Agreement Wanprestation in No. 537/Pdt.g/2013/PN.MDNAbstractInsurance is a legal term (legal term) used in legislation and insurance companies. The term insurance comes from the word "insurance" which means insurance or protection of an object from the threat of danger that causes loss. Insurance institutions are known in Indonesia since the entry of European countries to Indonesia. Insurance institutions officially enter Indonesia since the enactment of the Criminal Procedure Code which applies to Indonesia on the basis of the concordance principle contained in Stb. 1943 No. 23 which was promulgated on April 30, 1947, and entered into force on May 11, 1948. This type of research is normative juridical and analytical descriptive in nature. Sources of data obtained in this study through secondary data, and data analysis in the study using qualitative data analysis. Based on the results of research conducted by the author, insurance companies are only responsible for losses suffered by policyholders, if the loss is not made due to intentional. In agreements between insurance companies and agents, each has rights and obligations that must be carried out in good faith. Dispute settlement agency agreement is carried out with 4 stages, first, deliberation stage, second, warning stage, third, unilateral termination stage, fourth, compensation stage.